The development of the children’s psyche in early childhood and a psychological approach to raising children - Mirzayeva Xakimaxon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article reveals the factors of development in early childhood, the achievements in the child’s psyche, the development of intuition, memory, speech, thinking, perception, and the crises that occur during this period